2021
DOI: 10.1002/ejhf.2252
|View full text |Cite
|
Sign up to set email alerts
|

Treatment patterns and clinical outcomes among patients <65 years with a worsening heart failure event

Abstract: Aims Data regarding patients with chronic heart failure (HF) and reduced ejection fraction (HFrEF) following a worsening HF event (WHFE) are largely driven by findings from elderly patients. Younger patients are not well studied. The aim of this study was to evaluate treatment patterns and clinical outcomes in commercially insured chronic HFrEF patients <65 years old during 1‐year periods before and after a WHFE. Methods and results A retrospective claims analysis was performed using the IBM® MarketScan® Comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 18 publications
(35 reference statements)
2
9
0
Order By: Relevance
“…28,29 A national-level analysis comparing GDMT regimens 3 months before with those 3 months after a worsening HF event in patients with HFrEF reported similar rates of patients on one class of GDMT (29-29%), two GDMT classes (39-42%) and three GDMT classes (14-17%) following the worsening HF event, with these low rates persisting 1 year later. 30 In addition to reinforcing previous reports, that study provided a unique insight into the potential barriers to GDMT implementation. By studying younger patients with commercial insurance, it was found that low GDMT implementation is unlikely to be predominantly driven by medication intolerance due to advanced age, comorbidities or financial barriers.…”
Section: In-hospital Gdmt Initiation and Titrationsupporting
confidence: 70%
See 2 more Smart Citations
“…28,29 A national-level analysis comparing GDMT regimens 3 months before with those 3 months after a worsening HF event in patients with HFrEF reported similar rates of patients on one class of GDMT (29-29%), two GDMT classes (39-42%) and three GDMT classes (14-17%) following the worsening HF event, with these low rates persisting 1 year later. 30 In addition to reinforcing previous reports, that study provided a unique insight into the potential barriers to GDMT implementation. By studying younger patients with commercial insurance, it was found that low GDMT implementation is unlikely to be predominantly driven by medication intolerance due to advanced age, comorbidities or financial barriers.…”
Section: In-hospital Gdmt Initiation and Titrationsupporting
confidence: 70%
“…By studying younger patients with commercial insurance, it was found that low GDMT implementation is unlikely to be predominantly driven by medication intolerance due to advanced age, comorbidities or financial barriers. 30 Similarly, alerting providers to a patient's prognosis also did not improve GDMT prescription rates in a recent randomised trial, diminishing the likelihood that provider misunderstanding of prognostic risk is responsible for poor GDMT implementation. 31,32 GDMT initiation and titration during ADHF hospitalisation is an emerging strategy to increase both acute GDMT implementation and chronic adherence.…”
Section: In-hospital Gdmt Initiation and Titrationmentioning
confidence: 98%
See 1 more Smart Citation
“…The diagnosis of HFrEF was considered confirmed if at least one of the following criteria was met: a) one inpatient claim with an HFrEF diagnosis using the International Classification of Diseases, Tenth Revision (ICD-10) codes I50.2x, I50.4x, or I50.1; b) two outpatient claims for HFrEF; or c) one outpatient claim for HFrEF (I50.2x, I50.4x, or I50.1) plus one outpatient claim with any HF diagnosis (I50.1, I50.2x, I50.3x, I50.4x, I50.8x, I50.9, or I11.0) on two different dates within 12 months. 15,16 In addition, patients in our study population had to be continuously enrolled in a health plan for at least 12 months before and after the index date, with an allowed gap of fewer than 45 days between periods of continuous enrollment. Patients with evidence of heart transplant, a left ventricular assist device, adult congenital heart disease (eg, single ventricle disease), or amyloidosis prior to the index date were excluded.…”
Section: Study Populationmentioning
confidence: 99%
“…Pharmacotherapy is the cornerstone of treatment for HFrEF and is based on combined administration of drugs acting through different pathways 2,86–88 . However, implementation of the so‐called guidelines directed medical treatment (GDMT) remains suboptimal in a large proportion of patients 14,89–95 . In a multinational observational study, using healthcare databases in Sweden, the United Kingdom, and the United States, among new users of HFrEF drugs, over 12 month follow‐up, target doses of angiotensin‐converting enzyme inhibitors (ACEis), angiotensin receptor blockers (ARBs), beta‐blockers, and angiotensin receptor–neprilysin inhibitors (ARNIs) were achieved in 15%, 10%, 12%, and 30% of patients, respectively.…”
Section: Treatment Of Heart Failure With Reduced Ejection Fractionmentioning
confidence: 99%